2020
DOI: 10.1016/j.neo.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

MiR-944/CISH mediated inflammation via STAT3 is involved in oral cancer malignance by cigarette smoking

Abstract: Highlights Down-regulation of CISH in OSCC tissues and cell lines. CISH mediates cellular functions through STAT3 inhibition. MiR-944 regulates cellular functions through direct binding of CISH. Cigarette smoking-mediated miR-944/CISH/STAT3 axis plays a role in oral carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 75 publications
0
38
0
Order By: Relevance
“…1 d) and more details have been presented as Supplementary Data 1 . Further, we have also compared this data with another dataset (GSE37991) 37 41 in Supplementary Data 2 . Here, we also observe that both the datasets share a large number of vital DEGs and the pathways.…”
Section: Resultsmentioning
confidence: 99%
“…1 d) and more details have been presented as Supplementary Data 1 . Further, we have also compared this data with another dataset (GSE37991) 37 41 in Supplementary Data 2 . Here, we also observe that both the datasets share a large number of vital DEGs and the pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, miRNAs appear to play an important role in the development of smoking-related cancer. For example, cigarette smoking can induce miR-994 expression in oral cancer [ 28 ]. The expression of miR-21 was increased by cigarette smoke extract exposure in colorectal cancer [ 29 ], and the expression of this miRNA was elevated in esophageal cancers patients with consistent cigarette smoking [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al. [ 27 ] found that NNK upregulated the expression level of miR‐944 in OSCC cells. Furthermore, miR‐944 elicited pro‐inflammation cytokines secretion, migration, and invasion, ultimately promoting the OSCC process.…”
Section: Overview On Oscc and Chemoresistancementioning
confidence: 99%